Minimal Detectable Change for Gait Speed Depends on Baseline Speed in Individuals With Chronic Stroke. Issue 2 (April 2019) - Lewek, Michael D.; Sykes, Robert
Abstract : Background and Purpose: Given the heterogeneity of mobility outcomes after stroke, the purpose of this study was to examine how the minimal detectable change (MDC) for gait speed varies based on an individual's baseline walking speed. Methods: Seventy-six participants with chronic stroke and able to walk without therapist assistance participated in 2 visits to record overground self-selected comfortable gait speed (CGS) and fast gait speed (FGS). Based on the CGS at visit 1, participants were assigned to 1 of 3 speed groups: low (<0.4 m/s; n = 32), moderate (0.4-0.8 m/s; n = 29), and high functioning group (>0.8 m/s; n = 15). Participants were then reclassified using updated gait speed cutoffs of 0.49 and 0.93 m/s. For each group, we determined test-retest reliability between visits, and the MDC for CGS and FGS. Results: Gait speed significantly increased from visit 1 to visit 2 for each group ( P < 0.001). The reliability for CGS declined with increasing gait speed, and MDC95 values increased with increasing gait speed (low: 0.10 m/s; moderate: 0.15 m/s; and high: 0.18 m/s). Similar findings were observed for FGS, and when participants were recoded using alternative thresholds. Discussion and Conclusions: Slower walkers demonstrated greater consistency in walking speed from day to day, which contributed to a smaller MDC95 than faster walkers. These data will help researchers and clinicians adjust their expectations and goals when working with individuals with chronic stroke. Expectations for changing gait speed should be based on baseline gait speed, and will allow for more appropriate assessments of intervention outcomes. available: for more insights from the authors (see the Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A253 ). Abstract : Supplemental Digital Content is Available in the Text.